2018
DOI: 10.1007/s00441-018-2822-1
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membrane extract differentially regulates human peripheral blood T cell subsets, monocyte subpopulations and myeloid dendritic cells

Abstract: The discovery of the immunoregulatory potential of human amniotic membrane (hAM) propelled several studies focusing on its application for the treatment of immunological disorders. However, there is little information regarding the effects of hAM on distinct activation and differentiation stages of immune cells. Here, we aim to investigate the effect of human amniotic membrane extract (hAME) on the pattern of cytokine production by T cells, monocytes and myeloid dendritic cells (mDCs). For this purpose, periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In the case of phagocytosis, of note, by decreasing the ratio of HAECs:neutrophils, the phagocytic activity increased, as we observed the lowest and highest level of phagocytosis, respectively at the highest and lowest ratio of HAECs to neutrophils. These incompatible findings may be due to the fact that HAECs differentially regulate different populations of immune cells as it has been presented recently (26,27).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the case of phagocytosis, of note, by decreasing the ratio of HAECs:neutrophils, the phagocytic activity increased, as we observed the lowest and highest level of phagocytosis, respectively at the highest and lowest ratio of HAECs to neutrophils. These incompatible findings may be due to the fact that HAECs differentially regulate different populations of immune cells as it has been presented recently (26,27).…”
Section: Discussionmentioning
confidence: 98%
“…The present dominant view of HAECs is that they are immunomodulatory cells which express or secrete surface/soluble immunoreactive molecules ( 10 , 27 , 28 ). Some of these molecules such as HLA-G ( 29 ), PGE2 ( 30 , 31 ), IL-10 ( 32 ), and IDO ( 33 ) have already been shown that can influence neutrophils as well.…”
Section: Discussionmentioning
confidence: 99%
“…Second, studies have shown that AM could serve as an effective antibiotic reservoir when used in combination with antibiotics and provide sustained drug delivery 60 . Furthermore, AM has been shown to exhibit anti-inflammatory function via regulation of T-cell function and secretion of anti-inflammatory antagonists, including IL-1ra, sTNF, and VEGF-R 61 , 62 . This anti-inflammatory property will have a long-term beneficial effect on the cornea, hence vision, as persistent corneal vascularization could negatively affect the vision, either directly via encroachment on the visual axis or indirectly via lipid keratopathy where exudation of lipid and inflammatory cells extends to the visual axis 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of PGE2 production in DSCs rescued TNFα production, indicating that DSCs suppress Mφ TNFα production via PGE2. Conditioned media from amniotic membranes was added to peripheral blood immune cell subsets and responses characterized [94] and found that while T cells were skewed towards Th2 responses, blood monocytes exhibited CXCL10 suppression but no change to levels of TNF or IL-6. Use of activated or resting Mφ-conditioned media on CTBs of the fetal membranes induced changes in gene expression in leukocyte trafficking, adhesion, and cytokinerelated genes, all of which was independent of changes to DNA methylation and thus likely not due to epigenetic regulation [95].…”
Section: Methods To Study Paracrine Signaling In Fetal Membranesmentioning
confidence: 99%